Case of the Tarasov Mansion: Notes in the Margins of the Creative Biography of I. V. Zholtovsky - Pechenkin, Ilia E. (Actual Problems of Theory and History of Art, 2020)
The private house built for Gabriel Tarasov in Moscow (1909–1912) is one of the most remarkable pieces of the Russian 20th-century architecture. The article considers the Tarasov Mansion in the context of the I. V. Zholtovsky architectural practice of 1900–1920s. There is an interpretation of this building as a unique architect’s experience to renounce his creative individuality and to accurately reproduce the Palazzo Thiene at Vicenza (A. Palladio, 1542–1558). The overview of historiography gives an understanding of the sources of this interpretation, which is based on indifferent way for describing the composition of the main facade (which really has a striking resemblance to the palazzo at Vicenza) and the composition of the building as such. The author of the article proves that the Tarasov Mansion, firstly, is not a replica of the Renaissance prototype, but only contains quotes from its motive; and secondly, there is a similar method of citing and compiling the Renaissance sources in Zholtovsky designs and the buildings created both before and after work on the Tarasov Mansion. The manor houses of the early 20th century as well as the USSR pavilion at the Milan Fair (1925) or the Council House in Makhachkala (1926–1932) show that Zholtovsky did not inheritthe style only, but directly used the compositional solutions worked out by G. Romano, G. Vignola, and A. Palladio. Thus, the case of the Tarasov Mansion marks not a specific stage in the architect’s biography, but a fundamental characteristic of his professional method.
Keywords: architecture; Moscow; I. V. Zholtovsky; Tarasov Mansion; A. Palladio; method; Neoclassicism; Renaissance Revival architecture